2017
DOI: 10.1186/s12957-017-1118-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization in patients with metastatic spinal cord compression: mandatory or optional?

Abstract: BackgroundThe contribution of preoperative embolization in reducing intraoperative blood loss and its clinical importance are unclear. So, we aimed to compare the perioperative clinical outcomes based on whether preoperative embolization was performed and assess the role and safety of preoperative embolization in metastatic spinal cord compression (MSCC) patients.MethodsWe enrolled 52 patients (men, 37; women, 15) who underwent palliative decompression for MSCC. Demographic data, neurologic status, surgery-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
1
41
1
Order By: Relevance
“…However, massive bleeding (>2,000 mL) was significantly more frequent in the nonembolization group than in the embolization group. 6 Moreover, Rehák et al reported conflicting results as the embolized group presented with a significantly higher blood loss of 4,750 mL compared with 1,786 mL for the nonembolized group. Selection bias was likely present in this study, as tumor volume in the embolization wing was 2.5 times higher than that in the nonembolized group.…”
Section: Efficacy Reduction Of Intraoperative Blood Lossmentioning
confidence: 99%
See 3 more Smart Citations
“…However, massive bleeding (>2,000 mL) was significantly more frequent in the nonembolization group than in the embolization group. 6 Moreover, Rehák et al reported conflicting results as the embolized group presented with a significantly higher blood loss of 4,750 mL compared with 1,786 mL for the nonembolized group. Selection bias was likely present in this study, as tumor volume in the embolization wing was 2.5 times higher than that in the nonembolized group.…”
Section: Efficacy Reduction Of Intraoperative Blood Lossmentioning
confidence: 99%
“…Many studies report preoperative TAE can significantly reduce IBL and transfusion requirements. 6,34,35 In a recent case-control study, which matched patients with respect to age, surgery type, and tumor size, patients of the embolization group had less mean IBL (0.90 vs. 1.77L; p ¼ 0.002) and less packed red blood cell transfusion volume (2.15 vs. 3.56U; p ¼ 0.020), respectively, compared with those without preoperative embolization. 7 Conversely, other studies reported that IBL did not differ between the embolization and control groups.…”
Section: Efficacy Reduction Of Intraoperative Blood Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have verified the effectiveness of preoperative embolization in reducing intraoperative bleeding in spinal metastasis surgeries [ 85 - 87 ]. Surgery should be performed within 24 hours following embolization to avoid the diminished effect of preoperative embolization [ 88 ].…”
Section: Surgery For Metastatic Spinal Tumorsmentioning
confidence: 99%